1997
DOI: 10.1159/000169076
|View full text |Cite
|
Sign up to set email alerts
|

Experimental IgA Nephropathy Induced by Coxsackie B<sub>4</sub> Virus in Mice

Abstract: Viruses have been suspected to be etiological agents of IgA nephropathy. Recently, viruses were detected in renal tissues from patients with IgA nephropathy. We tried to cause lesions similar to IgA nephropathy by inoculating virus into mice and to detect virus RNA in the lesion by in situ hybridization. A group of mice were inoculated intravenously with coxsackie B4 virus once a month from 1 to 5 months of age and sacrificed monthly from 6 to 12 months of age. Mesangial proliferation and deposits t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…However, in the later samples, mesangial proliferation was improved, and the number of PAS-posi tive mesangial deposits decreased. The degree of mesan gial proliferation in this study was similar as compared with that in our previous study of repeated inoculation of CB4 [9], The observational period of mesangial prolifera tion in this study was relatively shorter than that of repeated inoculation of CB4 [9]. No obvious changes in mesangium were found in the control mice.…”
Section: Light-microscopic Findingssupporting
confidence: 85%
See 2 more Smart Citations
“…However, in the later samples, mesangial proliferation was improved, and the number of PAS-posi tive mesangial deposits decreased. The degree of mesan gial proliferation in this study was similar as compared with that in our previous study of repeated inoculation of CB4 [9], The observational period of mesangial prolifera tion in this study was relatively shorter than that of repeated inoculation of CB4 [9]. No obvious changes in mesangium were found in the control mice.…”
Section: Light-microscopic Findingssupporting
confidence: 85%
“…myo carditis, and myositis [14]. Moreover, these agents have been reported as the etiological agent in some renal dis eases [1][2][3][4][5][6][7][8][9]. For example, experimental nephritis induced by CB4 was first described by Sun et al [1], subsequent various reports have indicated a relationship of CB4 to renal disease in man and in experimental animals [2-5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been some speculation concerning renal injury by immune complexes (17,19). Immune complexes consist of anti- gen and antibody, and the antigen may be virus or renal tissue that is injured by viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…The renal tissue specimens were prepared by methods that were described previously by Yoshida et al (19).…”
Section: If Em and In Situ Hybridizationmentioning
confidence: 99%